2004
DOI: 10.1063/1.1639128
|View full text |Cite
|
Sign up to set email alerts
|

High thermal stability of magnetic tunnel junctions with oxide diffusion barrier layers

Abstract: We developed two types of magnetic tunnel junctions (MTJs) that showed high thermal stability. One is a PtMn exchange-biased spin-valve MTJ with a CoFe/Al-oxide (AlOx)/NiFe free layer and a CoFeTaOx/CoFe pinned layer, and the other is a pseudo-spin-valve (PSV) MTJ with a CoFe/AlOx/NiFe soft layer, where AlOx and CoFeTaOx act as barriers for Ni and Mn diffusion toward the tunnel barrier, respectively. After 390 °C-1H annealing, the PSV MTJs maintained 28% and the SV MTJs 39% of tunnel magnetoresistance. Transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…The TMR ratio of AlO x -based MTJ has been found to increase with annealing temperature (T A ) up to 265 • C [6]. However, Mn atoms diffuse toward the tunneling barrier (T A > 350 • C), reducing the TMR value [7].…”
Section: Introductionmentioning
confidence: 98%
“…The TMR ratio of AlO x -based MTJ has been found to increase with annealing temperature (T A ) up to 265 • C [6]. However, Mn atoms diffuse toward the tunneling barrier (T A > 350 • C), reducing the TMR value [7].…”
Section: Introductionmentioning
confidence: 98%
“…The magnetic behavior is very sensitive to chemical composition, interface and structure, and therefore, interdiffusion due to heat treatment may cause problems. Many Mn-metal alloys used as antiferromagnetic layer in magnetic device have been extensively studied [1][2][3]; however, the Mn atom causes interdiffusion problem to degrade the overall performance [4,5]. It was reported that the doping of Osmium (Os) may block the Mn diffusion channel up to 400 1C [6].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties of ultrathin NiFe layers sandwiched between Ta or Cu under and capping layers have been investigated and the reaction at the NiFe/Ta interface was shown to create a thick magnetic dead layer, 5,6) which can interfere with the H sw of MTJs after high-temperature treatments. On the other hand, we have already reported that a thin Al-oxide (AlO) layer can prevent interdiffusion between the NiFe and CoFe layers even after annealing at 400 C, 4) and we briefly demonstrated the same effect for AlO between NiFe and Ta layers, leading to a large improvement in the magnetic properties of NiFe after annealing at 400 C. 7) However, to date, the overall effect of capping layer materials with magnetoresistive properties in MTJ devices has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in the thermal robustness of MTJs have been reported mostly for magnetoresistance (MR) signal degeneration which is concerned with MRAM read operations. [1][2][3][4] Although attention should be given to MRAM write operations, the thermal robustness of the switching field (H sw ) in the MTJs of MRAM cell structures has not been adequately studied. The magnetic properties of ultrathin NiFe layers sandwiched between Ta or Cu under and capping layers have been investigated and the reaction at the NiFe/Ta interface was shown to create a thick magnetic dead layer, 5,6) which can interfere with the H sw of MTJs after high-temperature treatments.…”
Section: Introductionmentioning
confidence: 99%